Pediatric inflammatory multisystem syndrome temporally associated with COVID-19 - a novel condition in children and adolescents - Małgorzata Wieteska; Dominik Maj; Paweł Stanicki (Termedia Publishing House, 2021)
In March 2020, World Health Organization (WHO) declared the outbreak of the coronavirus disease 2019 (COVID-19) a pandemic. Pediatric inflammatory multisystem syndrome temporally associated with COVID-19 (PIMS-TS) also known as multisystem inflammatory syndrome in children (MIS-C) is a new phenomenon highly correlated with COVID-19. Recent research suggests that this new disease in children and adolescents is associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. It is a generalized inflammatory reaction suggestive of a likely autoimmune etiology. Symptoms of PIMS-TS are diverse and wide ranging. The disorder develops in children and adolescents as a result of dysregulation of the immune system, but the exact pathogenesis of PIMS-TS remains unknown. Consequently, the most effective types of therapy include supportive care, symptomatic and immunomodulating treatment. The ongoing international study of this condition may provide information on the treatment options, clinical trials and management process.